Pengaruh Motivasi Belajar, Kemampuan Pemecahan Masalah, dan Hasil Belajar Terhadap Kesiapan Kerja Siswa Kelas XII Pemesinan SMK Pemuda 3 Kesamben, Blitar - Rifqi Aziz (Jurnal Teknik Mesin dan Pembelajaran, 2020)
Abstract: Education is the quality improvement efforts of students to follow technological developments as well as add a breadth in order to be able to compete in further education or in the world of work. In an attempt to influence students in quality improvement by the motivation to learn, problem-solving ability, and the results of the study. This research aims to know the: (1) influence of Learning Motivation towards Work Readiness of students (2) Influences the ability of problem solving students ' Work against Italy (3) Influence the Learning Outcome against Italy work (4) influence of Learning Motivation, Ability of problem solving, and Learning Outcomes against the Work Readiness. This research is the research of ex post-facto. The subject of this research is the whole grade Machining XII SMK Pemuda 3 Kesamben, Blitar as much as 94 students. Now using the method of data collection and documentation. Test instrument of research carried out in the SMK Pemuda 3 Kesamben, Blitar. Testing analysis of the linearity test and the test covers multicollinearity. Data analysis technique used is a simple regression analysis  techniques to hepotesis first, second third hypothesis, hypothesis and regression analysis of the double for the fourth hypothesis. Based on the results of research on the first hypothesis of 75.7% which means the direct effect; the second hypothesis of 83.3% of the direct effect; the third hypothesis of 2.6% which means the effect is not immediate; whereas the fourth hypothesis of 23.3% to 65.7%, learning motivation for problem-solving ability, and 2.7% for the results of a study which means there is a direct and indirect influence against the working class XII student readiness Machining SMK Pemuda 3 Kesamben, Blitar. Keywords: The Motivation To Learn, Problem-Solving Abilities, Learning Outcomes, And Work Readiness